Azathioprine-induced marrow suppression in dermatology patients - Analysis of 18 patients - Vikrant V Saoji; Sugat A Jawade; Piyush Agrawal; Shravya Rimmalapudi (Indian Journal of Dermatology, 2022)
Background: Azathioprine is an immunosuppressant used to treat several immunological disorders. As a purine analog, it inhibits DNA synthesis and cell multiplication. However, marrow suppression is a serious complication associated with azathioprine. Aim: To analyze the marrow suppression caused by azathioprine in dermatology patients. Material and Method: This is a retrospective analysis of the records of 18 patients who presented with marrow suppression secondary to azathioprine which was used for the treatment of various dermatological diseases. Results: The analysis includes 18 patients, 15 females and 3 males with the average age being 25.88 years. All except two patients received 1 mg/kg of oral azathioprine once daily. Leukopenia was seen in 13 patients (with severe leukopenia in 7 patients), thrombocytopenia in 8, and low hemoglobin in 14 patients. Isolated low hemoglobin was seen in four patients, isolated leukopenia in four patients, and only one patient presented with isolated thrombocytopenia. Six patients had pancytopenia. The duration from the starting dose to reporting of marrow suppression ranged from 10 days to 1 year. Eight out of 18 patients presented with anagen effluvium, 2 patients with oral ulcers, and 1 patient with an upper respiratory tract infection. All the patients recovered within 1 month. Conclusion: Marrow suppression due to azathioprine can occur with a low dose of 1 mg/kg. Hair loss and oral ulcers serve as early warning signs for marrow suppression.